Advantages, Factors, Obstacles, Potential Solutions, and Recent Advances of Fish Germ Cell Transplantation for Aquaculture—A Practical Review - Jun Hyung Ryu; Lan Xu; Ten-Tsao Wong (Animals, 2022)
Germ cell transplantation technology enables surrogate offspring production in fish. This technology has been expected to mitigate reproductive barriers, such as long generation time, limited fecundity, and complex broodstock management, enhancing seed production and productivity in aquaculture. Many studies of germ cell transplantation in various fish species have been reported over a few decades. So far, surrogate offspring production has been achieved in many commercial species. In addition, the knowledge of fish germ cell biology and the related technologies that can enhance transplantation efficiency and productivity has been developed. Nevertheless, the commercial application of this technology still seems to lag behind, indicating that the established models are neither beneficial nor cost-effective enough to attract potential commercial users of this technology. Furthermore, there are existing bottlenecks in practical aspects such as impractical shortening of generation time, shortage of donor cells with limited resources, low efficiency, and unsuccessful surrogate offspring production in some fish species. These obstacles need to be overcome through further technology developments. Thus, we thoroughly reviewed the studies on fish germ cell transplantation reported to date, focusing on the practicality, and proposed potential solutions and future perspectives.